Ethnoornithology: Identification of bird names mentioned in Kakawin R?m?yana, a 9th-century Javanese poem (Java, Indonesia) - DEDE MULYANTO; JOHAN ISKANDAR; RIMBO GUNAWAN; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mulyanto D, Iskandar J, Gunawan R, Partasasmita R. 2019. Ethnoornithology: Identification of bird names mentioned in Kakawin R?m?yana, a 9th-century Javanese poem (Java, Indonesia). Biodiversitas 20: 3213-3222. Birds have played an important role in Javanese culture for a long time. For example, birds have been culturally used as sources of folk stories, myths, illustrated old manuscripts, paintings on relief walls of temples, and inspiration of writers to make poems. This article presents the results of an ethnoornithology study that tried to identify all bird names mentioned in Kakawin R?m?yana (KR), an old Javanese poem, using a qualitative method, mainly interpreting KR text based on an ethnoornithological approach. The results showed that 84 bird names are mentioned in the Kakawin R?m?yana, belonging to 26 families, and 17 orders. The birds mentioned in KR are predominantly residents, some are regular visitors or vagrant, and only a few are absent. The orders whose members appear most often are Passeriformes (18), Columbiformes (7), Pelecaniformes (6), Ciconiiformes (5), and Cuculiformes (5). There are only 13 names which are Sanskrit in origin. Based on this study, it can be inferred that birds have played an important role in Javanese culture.